POLA KEHIDUPAN WARIA DALAM MASYARAKAT JORONG MANDIANGIN NAGARI KATIAGAN KECAMATAN KINALI KABUPATEN PASAMAN BARAT - Susanki, Susanki; Oktavia, Dian Anggraini; Firdaus, Firdaus (Pendidikan Sosiologi, 2013)
Shemale is a clear and obvious irregularities, irregularities committed by transvestites difficulty in making established itself as a part of the community at large. Not all people can accept its existence despite the transsexual was allowed to live and settle in their communities The purpose of this study was to determine how the pattern of life in the midst of transgender people who do not fully accept its existence, and to analyze what are the factors that cause a person to be transgender in Jorong Mandiangin Kinali West Pasaman District.The approach used in this research is descriptive qualitative research, techniques used for data collection was done by direct observation and interviews, but it was also the study documentation. Techniques used in the selection of informants was purposive sampling, which consists of the informants who are considered to know about transgender life that is in Jorong Mandiangin. The subjects in this study were people who were in the neighborhood Jorong Mandiangin which include a government party, family transvestites, people who live close to the transvestite, transsexual close friends.This study describes the results of transgender life that reflects the good relationship between the transgender community and among transvestites. though people know that transgender is a real aberration , but not necessarily treat transgender people with no good treatment, people recognize that transgender people are also God s creation which also have the right to run their lives like other human beings. People can accept transsexuals in the environment where the transvestites in Mandiangin because never done a problem in the community, they run their lives by working in accordance with his ability. No different to life among fellow transvestites, seen the existence of a form of interaction processes that can unite the transvestites in maintaining gender status.